Sekolah Budaya Digital: Model Transformasi Pelestarian Budaya Lokal Berbasis Teknologi dan Eduwisata Komunitas - Ni Putu Puspa Widyastiti; Lilik Khomsatin Romadhoni; Ida Ayu Putu Widani Sugianingrat (Prosiding, 2025)
The preservation of local culture in the digital era faces serious challenges due to the strong current of globalization and the lack of innovation in methods of transmitting traditional values to younger generations. Elementary school children, particularly in rural areas, are increasingly disconnected from their cultural roots due to the absence of learning spaces suited to their characteristics as digital natives. This study proposes the concept of a “Digital Culture School” as an integrative strategy to strengthen cultural preservation, develop creative human resources, and promote community-based edutourism. The concept is based on a case study of the Pesinauan program in Kemiren Village, Banyuwangi—a traditional school initiated by the Osing community and conducted regularly every weekend. The method used is a conceptual-reflective approach, employing literature review and content analysis of Pesinauan documentation and relevant scholarly sources. The findings indicate that integrating direct cultural learning with the use of digital media can enhance children's participation, reinforce cultural documentation, and create a flexible and replicable educational model. In conclusion, the Digital Culture School has strong potential as an innovative solution to address the challenges of cultural preservation while serving as a community empowerment platform through the strengthening of cultural identity and the development of village-based educational tourism.